O devir da bioética: atrelado à história factual - Lepargneur, Hubert (Revista eclesiástica brasileira, 2007)
This article presents a global vision of the current stage of bioethics based on biomedical or technological researches and innovations that provided the author with materials for reflection. The hopes placed on the human DNA researches have still not produced the expected therapeutic improvements but bioethics is a long-term process that demands constant reevaluations. The innovations in the area, however, are numerous; we selected just a few. Whatever the anthropology underlying the collaborators’ minds may be, it guides a large part of the concrete conclusions; meanwhile, the philosophy of the principles must not make us forget the fundamental aspects of the situations and of the instruments it intends to orient.